Analisis Keputusan Pembelian Produk di Vending Machine FMIPA UII Menggunakan Regresi Logistik Berbasis Machine Learning - Muthia Rahmatun Nisa'; Faizal, Ade Ahmad; Edy Widodo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study examines factors influencing students’ purchasing decisions on vending machines using a statistical modeling approach. The increasing adoption of vending machines in university environments highlights the need to understand consumer decision-making within self-service systems. This research analyzes the effects of perceived ease of use and price perception on purchasing decisions for food and beverage products sold through vending machines at the Faculty of Mathematics and Natural Sciences, Universitas Islam Indonesia. Primary data were collected through an online questionnaire from 128 active students selected using purposive sampling. Instrument validity and reliability were assessed prior to analysis to ensure data quality. Given that the dependent variable is dichotomous, binary logistic regression was employed to estimate the probability of purchase decisions. The results indicate that perceived ease of use has a positive and statistically significant effect on purchasing decisions and serves as the most influential predictor in the model. Price perception also shows a positive and significant effect, although with a smaller magnitude. Overall, the model demonstrates acceptable classification performance. These findings suggest that improving system usability is more effective than price adjustments in increasing vending machine usage among students.